2010
DOI: 10.5152/jtgga.2010.28
|View full text |Cite
|
Sign up to set email alerts
|

Ruptured rudimentary horn pregnancy at sixteen weeks

Abstract: Pregnancy in a non-communicating rudimentary horn is very difficult to diagnose before it ruptures, leading to life -threatening intraperitoneal hemorrhage. A 22-year-old second gravida patient presented at the Emergency Center of the University Clinical Center of Kosova with a 16-week history of amenorrhea and acute onset of severe abdominal pain. She was resuscitated and taken for an emergency laparotomy under general anesthesia. Intraoperatively, there was a massive hemoperitoneum with a ruptured right rudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…22 Also rudimentary horn excision was found less cumbersome be it hematometra or a pregnancy in rudimentary horn. [22][23][24] Two cases of transverse vaginal septum resection were positive for tuberculosis on tissue biopsy. One resumed normal menstruation and next one had introital stenosis requiring graft to widen it.…”
Section: Discussionmentioning
confidence: 99%
“…22 Also rudimentary horn excision was found less cumbersome be it hematometra or a pregnancy in rudimentary horn. [22][23][24] Two cases of transverse vaginal septum resection were positive for tuberculosis on tissue biopsy. One resumed normal menstruation and next one had introital stenosis requiring graft to widen it.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 72 reports were selected for our analysis. [ 7 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 ] Most of the articles were case reports, and we found 103 cases published from January 2000 to November 2020. Two reviewers (W.I.…”
Section: Ethodsmentioning
confidence: 99%
“…[ 5 10 ] To treat these cases, emergency laparotomy is performed. Apart from detecting hypovolemic shock,[ 11 12 13 14 15 16 17 ] patients frequently have abdominal pain,[ 7 11 13 14 15 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 ] but some reports have indicated that only 8% of rudimentary horn pregnancies (RHPs) are diagnosed before the symptoms appear. [ 44 ] Sufficient knowledge seems necessary to detect NCRHP during early obstetric screening.…”
Section: Introductionmentioning
confidence: 99%